Comparison of Problem Based Learning and Realistic Mathematics Education to Improve Students Academic Performance - Batlolona, John Rafafy; Laurens, Theresia; Leasa, Marleny; Batlolona, Mariyam; Kempa, Rudolf; Enriquez, Javier Julian (FKIP Universitas Lampung, 2019)
Comparison of problem based learning and realistic mathematics education to improve student academic performance. Objectives: The aim of this study was to see an increase in the academic performance of island students in Ambon City by applying the problem based learning (PBL) learning model and realistic mathematics education (RME). Methods: This research was in the form of a descriptive qualitative study with a case study approach and a sample of 116 students. Findings: There was a significant increase in student academic performance at each meeting and learning outcomes with PBL were higher than RME. Conclusion: The PBL model is more effective in increasing students’ academic performance than RME because students were facilitated with onlinebased media in PBL when compared to RME, so that it can attract students’ attention in learning and have a significant impact on student academic performance. Keywords: Academic performance, problem-based learning, realistic mathematics education DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201921